Analytical Method Validation for the Determination of Tetrabutylammonium Bromide Content in Daclatasvir Dihydrochloride by LC-Ms/Ms - Suresh Reddy. Yellampalli (Journal of Global Pharma Technology, 2019)
Objective: A rapid, sensitive and selective analytical method was developed and validated for the determination of Tetrabutylammonium bromide content in Daclatasvir dihydrochloride. Method: Chromatographic separation was achieved on a Kinetex biphenyl 150X 4.6 mm, 5µm column using isocratic elution with the mobile phase consisting of acetonitrile and ammonium formate buffer with flow rate was 0.7 mL/min. Results: The retention time of Tetrabutylammonium bromide was found 4.65 min. The method was validated according to ICH [1] guidelines. The calibration curve was linear over the concentration range of 0.0310–0.1530 % (r = 0.9999). The intra- and inter-day precision (RSD %) was 3.8 % and the accuracy (%) was LOQ (91.8 %) to 150 % (101.6 %). Conclusion: The proposed method was simple, precise and accurate. The method can be used for the testing of content of Tetrabutylammonium bromide in Daclatasvir dihydrochloride API during routine quality control and stability testing.Keywords: LCMS/MS, Tetrabutylammonium bromide, Method validation, ICH guidelines and Daclatasvir dihydrochloride.